2004
DOI: 10.1002/poc.753
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the extraction of specific interaction enthalpy from the enthalpy of solvation

Abstract: A new, simple method for the extraction of specific interaction enthalpy from the enthalpy of solvation is proposed. It is based on empirical but very general relationships describing the non-specific solvation enthalpy. The specific interaction enthalpy is calculated from the solution enthalpies in the solvent under consideration, cyclohexane and tetrachloromethane. The solution enthalpy of at least one linear alkane in the solvent must also be available. The solution enthalpies of a 'model compound' or homom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 64 publications
2
44
0
Order By: Relevance
“…Neither approach was capable of predicting enthalpies of solvation in cyclohexane. Solomonov et al [13] proposed a simple method for extracting specific solutesolvent interactions from measured enthalpies of solvation. The method assumed that the difference between the nonspecific interaction contribution in the solvation enthalpy for the solute dissolved in the desired solvent and dissolved in cyclohexane was proportional to the difference in the nonspecific interactional solvation enthalpic contribution of the solute in solvents carbon tetrachloride and cyclohexane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither approach was capable of predicting enthalpies of solvation in cyclohexane. Solomonov et al [13] proposed a simple method for extracting specific solutesolvent interactions from measured enthalpies of solvation. The method assumed that the difference between the nonspecific interaction contribution in the solvation enthalpy for the solute dissolved in the desired solvent and dissolved in cyclohexane was proportional to the difference in the nonspecific interactional solvation enthalpic contribution of the solute in solvents carbon tetrachloride and cyclohexane.…”
Section: Resultsmentioning
confidence: 99%
“…Our search of the chemical literature found compilations of enthalpy of solvation data for 102 and 196 solutes dissolved in hexadecane [12] and cyclohexane [13,14], respectively, plus a large number of papers (which are listed in the Supplementary Material) that reported experimental partial molar enthalpies of solution of liquid and crystalline organic compounds in the four solvents of interest. The latter data were determined by either direct calorimetric methods or calculated based on the temperature dependence of measured infinite dilution activity coefficient data, and the published values were converted to gas-to-organic solvent enthalpies of transfer by Liquid solutes:…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It was found that the specific interaction enthalpies of H-donors in basic solvents are close to the enthalpies of 1:1 hydrogen bonding complexation in tetrachloromethane even for most polar bases [4]. Recently, Solomonov et al [10] suggested a novel general method to separate the specific interactions contribution from the enthalpy of solution/solvation. It allowed to calculate the enthalpy of specific interactions between solute and solvent for a wide range of systems, including a particularly interesting case of the enthalpy of self-association of aliphatic alcohols.…”
Section: Introductionmentioning
confidence: 97%
“…Widely recognized importance of this phenomenon for biochemical systems determines the necessity to have a method allowing to determine the energy of cooperative hydrogen bonding from experimental data. In a work [21], such method [10] was successfully applied for the enthalpies of cooperative hydrogen bonding. Now we are going to quantify the Gibbs energy of hydrogen bonding in solutions.…”
Section: Introductionmentioning
confidence: 98%
“…Depending on the standard state of the solute, either the sublimation enthalpy (D subl H) or the vaporization enthalpy (D vap H) is necessary to determine the solvation enthalpy: The specific interaction enthalpies, i.e., the enthalpies of solute-solvent interactions, are extracted using a method proposed very recently by Solomonov et al [11], based on empirical general relationships. Experimentally, the use of this method involves the knowledge of the solution enthalpies in the solvent under study, in cyclohexane, and in tetrachloromethane.…”
Section: Introductionmentioning
confidence: 99%